Efficiency enhancement in hybrid renewable energy system using polycrystalline silicon cell - Kumar, Mugachintala Dilip; Himabindu, D.; Kumar, Yarrem Narasimhulu Vijaya; Mohana, Thota; Shashank, Ramagiri; Rajanna, Bodapati Venkata (International Journal of Applied Power Engineering (IJAPE), 2024)
Accessing the unelectrified rural population is currently not possible through grid expansion, as connectivity is neither economically viable nor encouraged by large companies. Additionally, conventional energy options, such as broom-based systems, are being gradually phased out of rural development programs because to growing oil prices and the unbearable effects of this energy source on consumers and the environment. A hybrid generator using solar and wind can solve this issue. Proven hybrid systems are the best choice for delivering high-quality power. Nowadays, hybrid renewable energy systems are becoming popular. The power system provides electricity to remote and isolated areas. Villages and residents in the forest area had their electricity cut off due to the forest environment. While creating a renewable energy source near the load. Solar power and wind power are renewable sources, solar power works in the morning and wind can make morning and night time to synchronize both output voltage and frequency to provide provides the ability to charge continuously, without interruption. The main objective of the project is to provide mixed renewable energy without interruption.